Automatic detection of electricity pylons in aerial video sequences - Jittichat Tilawat (2018)
Automatic power transmission line inspection with aerial video surveillance requires that the vehicle-mounted camera can automatically locate electricity pylons. In this paper, a new approach for locating electricity pylons within video sequences is proposed. Straight lines in each video frame are extracted with a two-dimensional separable infinite impulse response (IIR) filter and the Hough transformation. A technique for selection of lines representing the electricity pylons is also proposed. The experimental results from a set of real-world video images are shown in term of the receiver operating characteristic (ROC) curve to verify the algorithm's detection performance. The ROC curve shows that the proposed algorithm performs very well and can very much help in the automatic electricity pylon detection system. © 2010 IEEE.